Spirituality in business ethics from an Islamic perspective - Mhd. Sarif, Suhaimi; Ismail, Yusof (IIUM Press, 2011)
This chapter explores the presence of spirituality in business ethics with the application of governing goodness and preventing evil. The foundation to spirituality in Islam is based on core perspective called Tawhid. The first element in Tawhidic paradigm(Unity of God) establishes the relationship not only with Allah(called vertical relationship), but also among human beings and the natural environment (called horizontal relationships). The second element is Tawhidic paradigm specifies a set of comprehensive,mutually reinforcing values referred to as promotion of goodness (‘amr bil ma’aruf) and prevention of evil (nahi anil munkar). It is important for decision makers – the servant (‘abd)and vicegerent (khalifa) - to comprehend this macro perspective upon which more specific principles are derived. The decision makers are obligated to integrate ma’aruf-munkar imperatives into the decision making process. Broad concept of ma’aruf incorporates goodness (khayr), righteousness (birr) and lawful (halal) which in turn deserve positive rewards (ajr). Munkar includes bad (sharr), sins (ithm) and prohibited (haram), which in turn are related to corresponding punishment ( i’dam).